Pengaruh Lingkungan Kerja dan Budaya Organisasi, Terhadap Motivasi serta Dampaknya pada Kinerja Guru Madrasah Aliyah - Syeikh, Saiyid; MS, M Zahari; Pamungkas, Bambang (Ekonomis: Journal of Economics and Business, 2024)
The government is creating a teacher certification program that will evaluate teachers' professionalism and determine how well they are able to perform their jobs in order to boost their desire to produce high-quality work. Researchers examine how organizational culture and environment affect teachers' performance and motivation in Madrasah Aliyah, West Tanjung Jabung Regency, West Part. This endeavor serves as a standard by which teachers are judged. Quantitative research was used to finish this study. The 39 samples that were used were chosen based on this research. Additionally, the description of the work environment, organizational culture, motivation, and performance of instructors at Madrasah Aliyah, East Tanjung Jabung Regency, West Region, is based on quantitative data collection and analysis using SPSS.